Economic burden of patients with diffuse large B-cell and follicular lymphoma treated in the USA. (18th June 2018) - Morrison, Vicki A; Bell, Jill A; Hamilton, Laurie; Ogbonnaya, Augustina; Shih, Huai-Che; Hennenfent, Kristin; Eaddy, Michael; Shou, Yaping; Galaznik, Aaron
Aim: Evaluate healthcare costs and utilization of treated diffuse large B-cell lymphoma (DLBCL) and follicular lymphoma (FL) patients.Materials & methods: Adults with newly diagnosed DLBCL and FL between 1 January 2008 and 31 October 2015 were identified in the Optum™ claims database. Healthcare costs and utilization were assessed from diagnosis date until end of follow-up.Results: A total of 1267 DLBCL- and 1595 FL-treated patients were identified. Mean per-patient, per-month cost during follow-up was US$11, 890 for DLBCL and US$10, 460 for FL. Healthcare costs and utilization decreased from year 1 to 2 following diagnosis, due to a decrease in chemotherapy services, inpatient admissions and other outpatient services.Conclusion: The economic burden of treated DLBCL and FL is considerable, especially in the first year following diagnosis.